Isolation and characterization of neutralizing monoclonal antibodies to vaccinia virus. - Rodriguez, J F (1985)
Cells producing neutralizing monoclonal antibodies (mAbs) to UV-inactivated vaccinia virus strain WR were derived by fusion of hyperimmunized mouse spleen cells with mouse myeloma cells. Three mAbs that reacted strongly with purified virus envelopes as determined by enzyme-linked immunosorbent assay were studied. The three mAbs recognized a 14,000-molecular-weight (14K) envelope protein of vaccinia virus and were shown to be immunoglobulin G2b (mAbC3 and mAbB11) and immunoglobulin M (mAbF11). By using ascites, one of the antibodies, mAbC3, neutralized (50%) virus infectivity with a titer of about 10(-4), whereas the others exhibited lower neutralization titers of 10(-2) to 10(-3). The binding of the mAbs to vaccinia virus did not alter virus attachment to cells. However, virus uncoating was extensively blocked by mAbC3, whereas mAbB11 and mAbF11 had little or no effect. The three mAbs recognized a similar 14K protein in cowpox, rabbitpox, and vaccinia Elstree strains, indicating a high degree of protein conservation among orthopoxviruses. Based on the binding of mAbs to V-8 protease cleavage products of the 14K protein, the extent of protein recognition for other poxviruses, and differences in the degree of virus neutralization and of virus uncoating into cells, we suggest that the three mAbs recognize different domains of vaccinia 14K viral envelope protein. Furthermore, our findings indicate that the 14K protein may play a role in virus penetration.